Key concepts of finance and investment - Kouadri, Missoun; Arif, Arif Ali; Artalim Zaim, Muntaha (Faculty of Management and Muamalah, KUIS, 2022)
One of the main tasks of the entrusted Sharia scholar is the full immersion in specialized scientific jurisprudence books to reveal the genuine concepts of scientific terminology which directly relate to the subject matter of his research; considering judging one matter is a part of its general conception. In identifying and defining concepts, which can only be achieved through exerting continuous effort, making it easier for the scholar to extract the juridical rule for an issue to be discussed. Therefore, this research is an attempt to link -to each other- the scientific and precise jurisprudence terminologies as much as possible, by clarifying and identifying the meaning of the terms finance and investment, in Islamic jurisprudence, and positive economics, and the relationship with their concepts; The research will adopt the inductive methodology; to investigate and illustrate the basic concepts included in the books of jurisprudence and positive economics about the terms finance and investment. Also, the research will use the analytical approach to highlight the relationship of the terms finance with investment.